Empowering preservice teachers’ pck development through resource folio pck development tools: Cores and pap-ers - Wiputra Cendana; Sean Patrick Kang; Dea Deviani Pradhipta (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Effective teaching entails PCK, enabling teachers to integrate different elements of instructional design in dynamic ways. The tacit nature of PCK poses challenges for novice teachers in understanding the reasons behind certain pedagogical approaches throughout the teaching-learning process. Resource Folio, as one of the PCK development tools that combines Content Representations (CoRes) and Pedagogical and Professional-experience Repertoires (PaP-eRs), is expected to be the solution for capturing teachers’ implicit pedagogical reasoning embedded in instructional design. This study investigates the use of the Resource Folio in developing and refining topic-specific PCK. 27 4th- to 6th-grade teachers in Tangerang were surveyed. The analysis of CoRes and PaP-eRs across the additional files reveals that teachers consistently use CoRes as a forward-planning pedagogical tool to align content knowledge, instructional strategies, and anticipated student difficulties, and PaP-eRs highlight teachers’ real-time decisions when students struggle, ask unexpected questions, or display alternative ways of thinking. The interaction between CoRes and PaP-eRs supports continuous pedagogical improvement rather than one-time lesson preparation. In conclusion, integrating CoRes and PaP-eRs fosters intentional instructional design, responsive teaching practices, and deeper student learning. This study provides a robust framework for developing reflective educators who can translate complex scientific concepts into meaningful, accessible learning experiences.